Psychological wellbeing in adult adoptees: current age and developmental tasks - Melero, Sandra; Verdugo, Laura; Sánchez-Sandoval, Yolanda (Frontiers in Psychology, 2023)
Introduction Studies about adult adoptees are normally focused on the differences in adjustment difficulties between them and non-adoptees. However, there has been less research about adoptees' positive and developmental adjustment in adulthood. The aim of this study is to test a model of the mediating role of adoptees' achievement of adulthood tasks in the relationship between current age and psychological wellbeing. Materials and methods The sample consisted of 117 adults who were adopted as children by Spanish families. Their current mean age is 28.3 years. Participants underwent an interview and completed Ryff's Psychological WellBeing Scales. Results Findings show that current age is directly and negatively related to psychological wellbeing [c′ = −0.039, 95% CI (−0.078, −0.001)], and the relationship between these variables is mediated by adoptees' achievement of adulthood tasks [indirect effect = 0.035, 95% CI (.014, 0.059)]. Discussion The findings support traditional theories about transitioning to adulthood, and adds relevant information about this transition in adoptees. Moreover, this work indicates a new way of assessing adoption success, based on long-term measures and normative variables. Services providers should account for the importance of supporting young people on their life transitions and promoting their wellbeing, especially among those who started from disadvantaged contexts.